Procedural outcomes and annual operator volume among patients treated with percutaneous coronary intervention of chronic total occlusions – analysis based on a large national registry. (3rd October 2022) - Januszek, R; Bryniarski, L; Siudak, Z; Malinowski, K P; Surowiec, S; Wanha, W; Wojakowski, W; Bryniarski, K; Legutko, J; Kambis, M; Di Mario, C; Bartus, K; et al.
Abstract: Background: It has been demonstrated that low operator and institutional volume is associated with poorer procedural and long-term clinical outcomes in general population of patients treated with percutaneous coronary interventions (PCI). Purpose: The aim of the current study was to assess the relationship between operator volume and procedural outcomes of patients treated with PCI within chronic total occlusion (CTO). Methods: Data for conducting the current analysis were obtained from the national registry of percutaneous coronary interventions (ORPKI) maintained in cooperation with the Association of Cardiovascular Interventions (AISN) of the Polish Cardiac Society. The study covered data obtained from the registry from January 2014 to December 2020. To investigate the association between operator and all periprocedural complications, coronary artery perforation (CAP) and TIMI flow grade 2/3 after PCI in the presence of confounding and clustering effects, we used multivariable, mixed effects logistic regression modelling. Results: During the investigated period, there were 162 active CathLabs, at which 747, 033 PCI procedures were performed during the time of observation. Of those 14, 924 were CTO-PCI procedures. Considering the number of CTO-PCIs performed annually by individual operators during the analyzed 7 years we assessed differences between four groups (≤10; >10≤20; >20≤30 and >30 procedures). We demonstrated by nonlinear relationship with annualised CTO-PCI operator volume that operators performing more than 40 PCI with CTO per year have lower number of the overall periprocedural complications (Fig. 1) including CAP, as well greater procedural success rates (Fig. 2) compared to operators performing less procedures (p<0.0001). Conclusions: High-volume CTO operators achieve a greater procedural success with a lower frequency of periprocedural complications. This study suggests that the cut-off of 50 CTO-PCIs per year recommended in the EuroCTO Consensus remains a reasonable compromise to optimize outcome and maintain local availability. Special CTO training programs and a higher annual case load might increase the overall quality of CTO PCI. Funding Acknowledgement: Type of funding sources: None.